A study on macroscopic fuel cladding ductile-to-brittle transition at 300°C induced by radial hydrides. Issue 3 (3rd March 2020) - Yamauchi, Akihiro; Ogata, Keizo
ABSTRACT: In this paper, to clarify the conditions for the occurrence of macroscopic hydrogen-induced ductile-to-brittle transitions (DBT) at operational temperatures, the effect of hydride precipitation on the mechanical properties of fuel cladding at 300°C was investigated. Tube burst tests were performed on the high-burnup Zr-lined Zircaloy-2 fuel cladding samples that were subjected to a hydrogen charging and hydride reorientation treatment. The precipitated hydrides had no significant effect on the cladding strength until the cladding lost its plasticity. Circumferential permanent strains at failure tended to decrease as the hydrides became longer, more densely precipitated, and more aligned to the radial direction. These results confirm that cladding ductility can be reduced significantly by hydrogen absorption even at 300°C if an extent of radial hydride formation is sufficiently high. Further, observations suggest that approximately 1% of the circumferential strain serves as a threshold for identifying the macroscopic hydrogen-induced DBT of the Zircaloy-2 cladding.